Developing a new department culture: when programs merge - William Hoon; Aimee Shouse (Academic Chairpersons Conference Proceedings, 2017)
This presentation will discuss some best practices that help transitioning cultures in merged or merging academic departments.
Keywords: department culture; merging; management; faculty